Augmented Reality di Museum Gedung Sate Bandung: Aksiologi Teknologi di Sektor Pariwisata - Anom, Rahmat Indra Pratama; Dewantara, Yudhiet Fajar; Pramanik, Purwanti Dyah; Djati, Sundring Pantja; Nurbaeti, Nurbaeti (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
In recent years, museums in Indonesia have innovated using Augmented Reality (AR) to compete with other tourist attractions. This study examines the benefits of AR innovation at the Gedung Sate Museum in Bandung. The research approach uses descriptive qualitative. Data obtained by conducting interviews, observation, and document analysis. This research involved 1 (one) operational staff of the Gedung Sate Museum and 7 (seven) visitors. The results of the study found that AR can increase the fun experience, increase knowledge, and simplify information acquisition for visitors. AR technology is recommended for use by the Gedung Sate Museum to attract the interest of the millennial generation who are very familiar with technology. Keywords: augmented reality, museums, axiology, tourism